Effectiveness of KTP-EL Services at the Bone Regency Population and Civil Registry Service - Maryadi Maryadi; Nawir Rahman (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2023)
KTP-EL aims to simplify the community identification process, but in its implementation, there are still several technical and administrative obstacles that must be overcome by the relevant agencies. This research aims to determine the effectiveness of KTP-EL services at the Bone Regency Population and Civil Registry Service. This type of research is qualitative using a descriptive approach. Data collection techniques were carried out by means of observation, interviews, and documentation. The data analysis technique used consists of data collection, data presentation, data condensation, and drawing conclusions. The results of the research show that the KTP-EL service at the Population and Civil Registry Service of Bone Regency is running effectively, this can be seen from 1) the existence of KTP-EL service procedures which are a reference in providing services to the community; 2) discipline of service officers, such as attendance, use of uniforms, work ethics and use of service tools; 3) provide services in Population Administration matters without charging fees; and 4) provision of adequate facilities and infrastructure, such as a large service area, sufficient chairs, and other facilities such as parking and toilets to provide comfort to the public